2018
DOI: 10.3389/fimmu.2018.02792
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor and miRNA-let-7e Expression Alter the Inflammatory Response in Leishmania amazonensis-Infected Macrophages

Abstract: Parasite recognition by Toll-like receptors (TLRs) contributes to macrophage activation and subsequent control of Leishmania infection through the coordinated production of pro-inflammatory and microbicidal effector molecules. The modulation of microRNA (miRNA) expression by Leishmania infection potentially mediates the post-transcriptional regulation of the expression of genes involved in leishmanicidal activity. Here, the contribution of TLR signaling to the miRNA profile and gene expression was evaluated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 98 publications
5
56
0
5
Order By: Relevance
“…However, the parasite can subvert the activation of macrophages to establish infection [36]. The genomic and transcriptomic networks during Leishmania infection have been providing interesting data regarding how Leishmania can to modulate the gene organization and gene expression of its host [37][38][39][40]. Additionally, we have observed differentially expressed genes profile during the different phases of parasite growth [37,38,41].…”
Section: Discussionmentioning
confidence: 83%
“…However, the parasite can subvert the activation of macrophages to establish infection [36]. The genomic and transcriptomic networks during Leishmania infection have been providing interesting data regarding how Leishmania can to modulate the gene organization and gene expression of its host [37][38][39][40]. Additionally, we have observed differentially expressed genes profile during the different phases of parasite growth [37,38,41].…”
Section: Discussionmentioning
confidence: 83%
“…Also, L. donovani strain, which is resistant to sodium stibogluconate, a pentavalent antimonial that is used for visceral leishmaniasis treatment in the Indian subcontinent, upregulates the expression of miR-466i in murine macrophages that target MyD88, increasing the levels of IL-10 production and the severity of disease [57]. Our group showed that the upregulation of let-7e, let-7f, and let-7g occurs in a MyD88, TLR2, or TLR4 dependent way during L. amazonensis infection and let-7e inhibition increases the expression of NOS2 mRNA, the NOS2 protein amount, and NO production, thus impacting infectivity [90]. Also, let-7e inhibition during L. amazonensis infection upregulates the levels of the validated targets, Tnfpaip3, Map2k4, Tbk1, and Tnf, as well as in the predicted targets, Traf 6, Ppara, Mapk8ip3/Jip3, Map3k1, and Ube2n, globally impacting TLR signaling gene expression [90].…”
Section: Leishmania-host Interactionsmentioning
confidence: 77%
“…Our group showed that the upregulation of let-7e, let-7f, and let-7g occurs in a MyD88, TLR2, or TLR4 dependent way during L. amazonensis infection and let-7e inhibition increases the expression of NOS2 mRNA, the NOS2 protein amount, and NO production, thus impacting infectivity [90]. Also, let-7e inhibition during L. amazonensis infection upregulates the levels of the validated targets, Tnfpaip3, Map2k4, Tbk1, and Tnf, as well as in the predicted targets, Traf 6, Ppara, Mapk8ip3/Jip3, Map3k1, and Ube2n, globally impacting TLR signaling gene expression [90]. It is interesting that the infection of macrophages with Mycobacterium and Neisseria upregulate the levels of let-7e [91,92].…”
Section: Leishmania-host Interactionsmentioning
confidence: 93%
“…The polyamine biosynthetic pathway has been described as critical to promote Leishmania intracellular replication inside host macrophages 6,18,19 . In this exploratory study, we performed a detailed investigation of the expression profiles of components of such pathway in skin lesions and in peripheral blood of patients presenting with distinct clinical forms within the spectrum of TL disease.…”
Section: Discussionmentioning
confidence: 99%